Analysis of Students’ Mathematical Problem-Solving Ability Based on Self-Confidence - Salsabila, Nahdah; Zakaria, Perry; Kobandaha, Putri Ekawaty (IKIP Siliwangi, 2025)
Education plays an important role in developing students’ potential, especially critical and creative thinking. Mathematics, as a core subject, supports students’ problem-solving ability, which involves understanding, procedure selection, and application in new contexts. One factor that may influence this ability is self-confidence, as confident students are more persistent and independent in solving problems. This study aimed to examine the effect of self-confidence on students’ mathematical problem-solving ability. The research employed a quantitative correlational design with a purposive sample of 60 seventh-grade students at SMP Negeri 8 Kota Gorontalo. Instruments consisted of a mathematical problem-solving test and a self-confidence questionnaire. Data were collected through tests and questionnaires, then analyzed using simple linear regression and correlation coefficient tests. The findings revealed that self-confidence significantly affects students’ mathematical problem-solving ability. Students with higher self-confidence tended to achieve better outcomes. The correlation coefficient was 0.6923 (strong positive), with a coefficient of determination (R²) of 47.22%, indicating that self-confidence contributed nearly half of the variation in problem-solving ability. The remaining 52.78% was influenced by other factors not examined in this study, such as math anxiety, learning habits, and environmental support. In conclusion, self-confidence has a positive and significant effect on mathematical problem-solving ability, suggesting the importance of fostering students’ confidence alongside academic skills.